Solid-type adenoid cystic carcinoma of the breast, a distinct molecular entity enriched in NOTCH and CREBBP mutations - Massé, Julie; Truntzer, Caroline; Boidot, Romain; Khalifa, Emmanuel; Pérot, Gaëlle; Velasco, Valérie; Mayeur, Laétitia; Billerey-Larmonier, Claire; Blanchard, Larry; Charitansky, Hélène; Soubeyran, Isabelle; Iggo, Richard; et al. (Modern pathology, 2020)
Adenoid cystic carcinoma (ACC) of the breast with a predominant solid pattern is difficult to diagnose with certainty and differentiate from more common triple-negative breast cancers (TNBCs) of basal-phenotype. To better characterize solid ACC, we performed a clinical, morphological, immunohistochemical, and molecular comparative analysis of 33 ACCs of the breast comprising 17 solid variant ACCs and 16 conventional ACCs. Solid ACCs displayed basaloid morphology with an exclusive or predominant epithelial cell population associated with decreased myoepithelial differentiation, while demonstrating MYB protein overexpression similar to the more common type of ACC. Strong and diffuse MYB expression by immunochemistry was observed in 14/17 (82%) of solid ACCs while MYB rearrangements were detected by break apart fluorescence in situ hybridization (FISH) in only 3/16 (19%) of solid ACCs. Conversely, weak MYB immunohistochemical expression was observed in only 7/204 (3%) of TNBC. Solid ACCs displayed a transcriptomic profile distinct from conventional ACCs with 549 genes showing a highly significant differential expression between conventional and solid ACC [false discovery rate (FDR) < 0.01; log2FC > |1|]. EnrichR and Kegg Pathway analyses identified PI3K-Akt and focal adhesion signaling pathways as significantly overexpressed in conventional ACCs compared with solid ACCs which significantly overexpressed the nitrogen metabolism pathway. CREBBP mutations and NOTCH activating gene mutations were only present in solid ACCs, concerning 5/16 (31%) of cases for each gene. Tumors with NOTCH activating mutations displayed a strong diffuse nuclear NICD1 staining, an established marker of Notch pathway activation. Solid ACCs also differed from basal-type TNBC, with fewer TP53 mutations and a more stable genomic profile on array comparative genomic hybridization (CGH). In summary, solid-type ACC of the breast is a distinct molecular entity within the ACC family and is different from common basal-type TNBC. MYB is a diagnostically useful biomarker of solid ACC and NOTCH could be a novel potential therapeutic target in 30% of cases.